Don't forget to write for the secondary grades : 50 enthralling and effective writing lessons : ages 11 and up - Traig, Jennifer (Jossey-Bass, 2011)
Getting your students excited about writing begins with offering projects that are interesting, relevant, and challenging. This book offers 50 creative writing lesson plans for mature young writers developed by the imaginative and highly acclaimed 826 National writing centers. These lessons cover a myriad of skills (developing characters and voice), interests (novel-writing, song- writing, screenwriting), and even interest levels. (Don't believe us? try out "This Class Sucks" or "My Boring Life" for those especially hard-to-reach writers.) Each unique lesson is written by educators, 826 volunteers, celebrated authors, actors, and writers.--Adapted from back cover.